2019
DOI: 10.1111/sum.12527
|View full text |Cite
|
Sign up to set email alerts
|

Plant availability of magnesium and phosphorus from struvite with concurrent nitrification inhibitor application

Abstract: Struvite (MgNH4PO4.6H2O) and nitrification inhibitors are applied to soils to, respectively, provide nutrients and reduce nitrogen (N) loss. Given its low N composition (5.7%) relative to that of phosphorus (P, 12.6%) and magnesium (Mg, 9.9%), struvite could be added to soil concurrently with N fertilizers as a source of P and Mg. Nutrient release from struvite could be impacted if nitrification of its ammonium component is reduced by a nitrification inhibitor. Accordingly, a pot trial gauged whether struvite‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…This is in line with Vogel et al (2015), where available P pools in soil increased after struvite application and struvite was considered to be an effective P source for several different plants. Recently, the struvite used in the present experiment was shown to be a very good source of P and Mg to ryegrass (Watson et al 2019). However, in our experiment, only a small proportion of applied P was found in the plant biomass at the end of our experiment, which may have been due to reduced plant growth as caused by other limiting nutrients or by satisfied P demand of the growing plants.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…This is in line with Vogel et al (2015), where available P pools in soil increased after struvite application and struvite was considered to be an effective P source for several different plants. Recently, the struvite used in the present experiment was shown to be a very good source of P and Mg to ryegrass (Watson et al 2019). However, in our experiment, only a small proportion of applied P was found in the plant biomass at the end of our experiment, which may have been due to reduced plant growth as caused by other limiting nutrients or by satisfied P demand of the growing plants.…”
Section: Discussioncontrasting
confidence: 65%
“…However, this was not observed in the roots, where control plants had a higher Mg:Ca ratio and the P:Mg ratio did not differ. The role of struvite as magnesium source requires more investigation as mentioned earlier (Watson et al 2019).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Vogel et al (2017) reported the superior field growth of struvite-fertilised forage rye and sorghum to plants receiving triple superphosphate (TSP) and attributed this to a positive magnesium effect. Watson et al (2019) demonstrated struvite to effect a superior Mg uptake in ryegrass when compared with a commercially available magnesium sulphate fertiliser. Kataki et al (2016) noted Mg concentrations in soils might rise following repeated struvite amendment; this was acknowledged as potentially disruptive to Ca nutrition but beneficial to P uptake.…”
mentioning
confidence: 96%